Synthesis and crystallographic characterization of diphenylamide rare-earth metal complexes Ln(NPh2)3(THF)2 and [(Ph2N)2Ln(μ-NPh2)]2 - Chad T. Palumbo; Christopher M. Kotyk; Joseph W. Ziller; William J. Evans (Acta Crystallographica Section E: Crystallographic Communications, 2020)
Studies of the coordination chemistry between the diphenylamide ligand, NPh2, and the smaller rare-earth LnIII ions, Ln = Y, Dy, and Er, led to the structural characterization by single-crystal X-ray diffraction crystallography of both solvated and unsolvated complexes, namely, tris(diphenylamido-κN)bis(tetrahydrofuran-κO)yttrium(III), Y(NPh2)3(THF)2 or [Y(C12H10N)3(C4H8O)2], 1-Y, and the erbium(III) (Er), 1-Er, analogue, and bis[μ-1κN:2(η6)-diphenylamido]bis[bis(diphenylamido-κN)yttrium(III)], [(Ph2N)2Y(μ-NPh2)]2 or [Y2(C12H10N)6], 2-Y, and the dysprosium(III) (Dy), 2-Dy, analogue. The THF ligands of 1-Er are modeled with disorder across two positions with occupancies of 0.627 (12):0.323 (12) and 0.633 (7):0.367 (7). Also structurally characterized was the tetrametallic ErIII bridging oxide hydrolysis product, bis(μ-diphenylamido-κ2N:N)bis[μ-1κN:2(η6)-diphenylamido]tetrakis(diphenylamido-κN)di-μ3-oxido-tetraerbium(III) benzene disolvate, {[(Ph2N)Er(μ-NPh2)]4(μ-O)2}·(C6H6)2 or [Er4(C12H10N)8O2]·2C6H6, 3-Er. The 3-Er structure was refined as a three-component twin with occupancies 0.7375:0.2010:0.0615.